Analysis of Ornamental Fish Farming Member Of Group Diamond Fish Club In Tampan Village Districts Payung Sekaki Pekanbaru City Riau Province - Anggina, Debby; Hamid, Hamdi; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 14 th May until 21 th May 2013. This study aims todetermine how much capital invested by ornamental fish farmers, the total of cost production, andrevenues and profits business member Diamond Fish Club. The method used in this study is asurvey method with six respondents.The results of this study indicate the average total investment in the plant by ornamental fishfarmers is Rp 11.128.367,-/harvest. The average total of cost production (TC) of Rp 4.672.672,-/harvest and the average revenue earned by farmers Rp 9.357.833,-/harvest with an averagebusiness profit of Rp 4.685.161/harvest.Keyword : Tampan Village, Total Investment, Ornamental Fish